Thymoma: a case report and review of the literature - Hamidah A; Poulsaeman V; Suria AA; Zarina AL; Zulfiqar MA; Jamal R (Penerbit UKM, 2010)
Thymomas comprise about 1% of all mediastinal tumours and are rare in children. Typically, these tumours are aggressive, with a poor outcome. The current treatment of invasive thymoma is often multidisciplinary. We report a 16-year-old boy with invasive thymoma who was successfully treated with systemic chemotherapy, surgical resection and irradiation. The patient has been in continuous remission for 6 years without radiographic evidence of tumour recurrence.